Hsa_circRNA_103124 Upregulation in Crohn’s Disease Promotes Cell Proliferation and Inhibits Autophagy by Regulating the Hsa-miR-650/AKT2 Signaling Pathway - Yin, Juan; Tong, Fuyi; Ye, Yulan; Hu, Tong; Xu, Lijuan; Zhang, Liping; Zhu, Jianyun; Pang, Zhi (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) play important roles in the pathogenesis of Crohn’s disease (CD). We discovered that hsa_circRNA_103124 was upregulated in CD patients in our previous study. Nonetheless, the function of hsa_circRNA_103124 is unclear. In this study, hsa_circRNA_103124 was predicted to interact with hsa-miR-650. Gene Ontology (GO) and pathway analyses identified AKT serine/threonine kinase 2 (AKT2) as the downstream target protein of hsa-miR-650. Activated AKT2 inhibits autophagy, but promotes cell proliferation. Recent studies suggest that the inhibition of autophagy is one of the mechanisms of CD pathogenesis. Therefore, we inferred that hsa_circRNA_103124 might regulate autophagy and proliferation by targeting AKT2 as a sponge for hsa-miR-650. Here, quantitative reverse transcription PCR (RT-QPCR) results revealed that upregulated hsa_circRNA_103124 expression in patients with CD was negatively correlated with hsa-miR-650 expression but positively correlated with the white blood cell count and calprotectin levels. TSC complex subunit 1 (TSC1), one of the proteins upstream of autophagy was downregulated in patients with CD. Consisting with the bioinformatics prediction, it was verified that hsa_circRNA_103124 targeted to hsa-miR650 by fluorescence in situ hybridization (FISH) and luciferase reporter assays. A hsa-miR-650 inhibitor reversed the promotion of rapamycin-induced autophagy and the inhibition of cell proliferation by the hsa_circRNA_103124 siRNA. However, hsa-miR-650 mimics reversed the inhibition of rapamycin-induced autophagy and the promotion of cell proliferation through hsa_circRNA_103124 overexpression. These results indicate that hsa_circRNA_103124 upregulation in patients with CD promotes cell proliferation and inhibits autophagy by regulating the hsa-miR-650/AKT2 signaling pathway.